Cobalt Catalysis for Enantioselective Cyclobutanone Construction - Kim, Daniel K. (J Am Chem Soc, 2017)
Over the past forty years, intramolecular hydroacylation has favored five-membered rings, in preference to four membered rings. Herein, we report a catalyst derived from earth abundant cobalt salts that enables preparation of cyclobutanones, with excellent regio-, diastereo-, and enantiocontrol, under mild conditions (2 mol% catalyst loading and as low as 50 °C).